Bella ciao [videorecording] - Bagong Alyansang Makabayan; Kilusang Mayo Uno.; Partido ng Bayan (Quezon City Asia Visions, 1986)
A documentary on the life, struggle and death of labor leader, Ka Lando Olalia.
Keywords: Olalia, Rolando; Biography; Labor relations